Spazio, tempo, sé: nuove ontologie digitali - FUSCHETTO, CRISTIAN (S&F_scienzaefilosofia.it, 2017)
Space, Time, Self: new digital Ontologies The digital is deeply transforming reality. This is much obvious and uncontroversial. The real questions are why, how, and so what. The digital “cuts and pastes” reality, in the sense that it couples, decouples, or recouples features of the world—and therefore our corresponding assumptions about them—which we never thought could be anything but indivisible and unchangeable. Self-identity and personal data have not always been glued together as indistinguishable as they are today, when we speak of personal identity of data subjects. he Internet is not a physical space, the physical space of geography, and the logical space of the digital. This is a new, variable “geometry” that we are still learning to manage.